Rol de las redes sociales en la campaña “si pero no” ¿qué mismo es el amor tóxico? de la Universidad Politécnica Salesiana. - Novoa Pérez, Yadira Ximena (2018)
Digital social networks offer the possibility of deliberating and coordinating unfettered actions, it is only one element of the communicative processes through which social movements relate to society in general, this research belonging to the Communication and Communication research line. Citizenship, with a qualitative-quantitative approach, of descriptive type with support in the theory of netnography in the qualitative aspect, the socio-technical analysis was applied, and the theory of the actor-network, aimed to describe the role of networks in the Campaign "Si, pero No” ¿Qué mismo es el amor tóxico? of the Salesian Polytechnic University and it was concluded that the campaign as a case study, through the alternative media was very effective when doing an activity of connection with society, was able to show at a given moment in the Salesian Polytechnic University the violence of gender and what this means, the alternative media were more effective at the time of spreading the campaign, something that did not happen with social networks, since social networks were not relevant actors in the dissemination and communication of the same, the analysis technical partner and the theory of the network actor demonstrated in the research how the social influence on technology and this on the societies.